Non-metal doped titanium-based metal monatomic electrode for decomplexing complex-state heavy metal and preparation method and application of non-metal doped titanium-based metal monatomic electrode

By introducing non-metal doped and metal single atoms on the titanium-based material, a high-performance non-metal doped titanium-based metal single atom electrode is solved, and the problems of poor bursting activity and insufficient stability of the anode material in the prior art are solved. The deep treatment of complex heavy metals and the recycling of heavy metal resources are realized.

CN119430401AActive Publication Date: 2025-02-14SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411702272.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the prior art, electrochemical anode materials have poor activity and insufficient stability in complexed heavy metals, making it difficult to achieve deep treatment of complexed heavy metals and recycling of heavy metal resources.

Method used

Using a non-metal doped titanium-based metal single-atom electrode, the metal single-atom sites are fixed on the surface of the material and electrons that regulate metal are introduced by the strong bonding interaction between the inherent oxide layer on the surface of the titanium-based material. Structure, improve the stability and bursting performance of metal sites.

Benefits of technology

It realizes high-performance anode material, can effectively break a variety of complex heavy metals, has good stability, and is suitable for the deep treatment of complex wastewater in complexed industries and the recovery of heavy metal resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430401A_ABST
    Figure CN119430401A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of heavy metal complex wastewater treatment, and particularly relates to a non-metal doped titanium-based metal monatomic electrode for decomplexing complex-state heavy metals and a preparation method and application thereof, the non-metal doped titanium-based metal monatomic electrode comprises a titanium substrate, and non-metal atoms and metal monatomic which are respectively loaded on the surface of the titanium substrate; the non-metal atoms are selected from one or more of phosphorus, boron and sulfur; the metal single atoms are selected from one or two of iron and cobalt. Compared with the prior art, the problems that in the prior art, an electrochemical anode material is poor in activity and insufficient in stability when breaking complex-state heavy metal are solved, the strong bonding interaction between an inherent oxide layer on the surface of the titanium-based material and a metal monatomic site is utilized, and metal monatomic is fixed to the surface of the material; meanwhile, nonmetal is introduced to regulate and control an electronic structure of metal, so that the metal site stability and decomplexing performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heavy metal complex wastewater treatment, and specifically relates to a non-metal-doped titanium-based metal single-atom electrode for decomplexing complexed heavy metals, and a preparation method and application thereof. Background Art

[0002] The annual discharge of heavy metal wastewater from industries such as metal smelting, electrolysis, electroplating, and chemical cleaning is as high as one million tons. Heavy metals are usually present in the form of stable complexed heavy metals (such as Ni(II)-EDTA), and traditional water treatment technologies such as precipitation and adsorption are difficult to achieve deep removal. In the context of sustainable development, considering that complexed heavy metals are valuable metal resources, it is urgent to develop effective treatment methods for complexed heavy metal decomposition and metal resource recovery.

[0003] Electrochemical decomposition of complexed heavy metals uses electrons and water as green reaction reagents, is mild and controllable, and has received more and more widespread attention. The active species produced by electrochemical anodic oxidation can selectively destroy complex ligands, release heavy metal ions, and then reduce and recover heavy metals at the cathode. However, the anode is easily competed with the oxygen evolution side reaction during the decomposition process, which inhibits the decomposition performance; at the same time, the metal active sites are easily peroxidized, which causes metal dissolution and leads to decreased electrode stability.

[0004] In the prior art: CN114162907A discloses a single-atom electrode and its preparation method and application, the electrode comprises a metal substrate and a native oxide layer on its surface, the native oxide layer is defect-rich, and metal single atoms are anchored at the defects; the preparation method comprises the following steps: (1) treating the metal with a native oxide layer on its surface at high temperature in a reducing atmosphere to form a defect-rich metal substrate; (2) dripping a metal precursor solution onto the defect-rich substrate surface, drying it, and then treating it at high temperature in a reducing atmosphere to obtain a single-atom electrode, which can be used for catalytic treatment of wastewater. CN115925056A discloses a preparation method of a phosphorus-doped titanium oxide / foam titanium electrode and a method for treating heavy metal wastewater. The preparation method is as follows: the titanium dioxide / foam titanium electrode is cleaned and placed in a tubular furnace in which sodium hypophosphite and the titanium dioxide / foam titanium electrode are placed in the order of inert gas flow, and inert gas is introduced and heat treated at 300-350° C. During the heat treatment, the inert gas first passes through the sodium hypophosphite, then passes through the titanium dioxide / foam titanium electrode and is discharged from the tubular furnace; finally, the tubular furnace is naturally cooled to room temperature, and post-processed to obtain a phosphorus-doped titanium dioxide / foam titanium electrode.

[0005] However, CN114162907A emphasizes the use of reducing atmosphere to treat the titanium substrate surface to obtain a defect-rich oxide layer, and then anchoring metal single atoms to synthesize single-atom electrodes in two steps. The overall synthesis process is complex and demanding. CN115925056A prepared phosphorus-doped sub-titanium oxide / foam titanium electrodes by pyrolyzing phosphorus precursors. The patent did not find that metal single atoms can be loaded simultaneously during the non-metallic doping process; nor did it study whether other non-metallic doping can improve the electrochemical decomposition performance of sub-titanium oxide.

[0006] Therefore, the development of a high-performance anode is crucial for the deep treatment of complexed heavy metal industrial wastewater and the recycling of heavy metals. Summary of the invention

[0007] The purpose of the present invention is to solve at least one of the above problems and to provide a non-metal-doped titanium-based metal single atom electrode for decomplexing heavy metals and its preparation method and application, so as to solve the problem of poor activity and insufficient stability of electrochemical anode materials in decomplexing heavy metals in the prior art. This scheme utilizes the strong bonding interaction between the inherent oxide layer on the surface of the titanium-based material and the metal single atom sites to fix the metal single atoms on the surface of the material, and at the same time introduces non-metals to regulate the electronic structure of the metal, thereby improving the stability of the metal sites and the decomplexing performance.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] The first aspect of the present invention discloses a non-metal-doped titanium-based metal single atom electrode for decomplexing heavy metals, comprising a titanium substrate, and non-metal atoms and metal single atoms respectively loaded on the surface of the titanium substrate;

[0010] The non-metal atom is selected from one or more of phosphorus, boron and sulfur;

[0011] The metal single atom is selected from one or both of iron and cobalt.

[0012] Preferably, the titanium substrate includes titanium mesh, titanium felt and titanium foam; the doping amount of the non-metallic atoms is 0.02-0.5wt% of the total mass of the electrode; and the doping amount of the metal single atom is 0.02-0.5wt% of the total mass of the electrode.

[0013] Preferably, the area of ​​the titanium substrate is 0.01 to 1 m 2 .

[0014] The second aspect of the present invention discloses a method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals as described above.

[0015] If the non-metal atom is phosphorus and / or sulfur, the preparation method comprises the following steps:

[0016] Placing a non-metallic precursor solution at the air inlet of a tube furnace; uniformly dripping a metal precursor solution on the surface of a titanium substrate, and placing it at the air outlet of a tube furnace after drying; performing pyrolysis under a protective atmosphere to obtain the electrode;

[0017] If the non-metal atom is boron, the preparation method comprises the following steps:

[0018] The metal precursor solution is evenly dripped onto the surface of the titanium substrate, and then the non-metal precursor solution is dripped onto the surface of the titanium substrate, and infrared heating and pyrolysis are performed under a protective atmosphere to obtain the electrode.

[0019] Preferably, the metal precursor solution is a chloride, nitrate or acetate of a metal, and the concentration of the metal precursor solution is 0.5-10 mg / mL.

[0020] More preferably, the concentration of the metal precursor solution is 1 mg / mL.

[0021] Preferably, the non-metal precursor solution: if the non-metal atom is phosphorus, the non-metal precursor is phosphite; if the non-metal atom is sulfur, the non-metal precursor is at least one of thiourea, sodium sulfide and sulfur powder; if the non-metal atom is boron, the non-metal precursor is boric acid or boron oxide; the concentration of the non-metal precursor solution is 3 to 30 mg / mL.

[0022] Preferably, if the non-metal atom is phosphorus and / or sulfur, the mass ratio of the non-metal precursor to the metal precursor is 2-12:1; if the non-metal atom is boron, the mass ratio of the non-metal precursor to the metal precursor is 1-6:1.

[0023] More preferably, if the non-metal atom is phosphorus and / or sulfur, the mass ratio of the non-metal precursor to the metal precursor is 4:1; if the non-metal atom is boron, the mass ratio of the non-metal precursor to the metal precursor is 1:1.

[0024] Preferably, the protective atmosphere is an argon atmosphere and / or a nitrogen atmosphere.

[0025] Preferably, the pyrolysis temperature is 200-500° C. and the time is 2-5 hours.

[0026] More preferably, the pyrolysis temperature is 300° C. and the time is 3 h.

[0027] The third aspect of the present invention discloses the use of the non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals as described above in the treatment of heavy metal complex wastewater.

[0028] Preferably, the heavy metal complex includes but is not limited to one or more of nickel ethylenediaminetetraacetate, copper ethylenediaminetetraacetate and chromium ethylenediaminetetraacetate, and the concentration of the heavy metal complex in the wastewater is 10 to 100 mg / L.

[0029] Preferably, a three-electrode system is used for electrochemical decomposition;

[0030] In the three-electrode system:

[0031] The working electrode is the electrode as described above; the reference electrode is selected from a silver-silver chloride electrode; the counter electrode is selected from one of carbon felt, carbon cloth, graphite sheet and titanium mesh; the electrolyte is a sodium sulfate solution (0.01-0.5 mol / L);

[0032] In the electrochemical network breaking:

[0033] The applied voltage is 0.8 to 3.0 V, and the reaction time is 1 to 3 hours.

[0034] The working principle of the present invention is:

[0035] Under power-on conditions, the metal atoms on the anode will be oxidized from a low-valent state to a high-valent state, transforming into species with high oxidative activity. These active species can attack and destroy the coordination bonds of the complex formed by heavy metal ions and EDTA, thereby achieving the decomposition of the complex. Subsequently, the heavy metal ions dissociated from EDTA will be reduced to the corresponding metal elements at the cathode. In this process, the doping of non-metallic atoms can effectively adjust the electronic structure of the anode metal atoms and enhance their stability on the anode substrate, thereby showing a long-lasting complex decomposition efficiency.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The preparation method of the non-metal-doped titanium-based metal single atom electrode disclosed in the present invention is simple. By pyrolyzing the non-metal precursor and reacting with the surface oxide of the titanium substrate, the non-metal and metal single atoms are synthesized into a non-metal-doped metal single atom electrode in one step. The process is simple, efficient, easy to industrially scale up, and feasible for large-scale preparation.

[0038] 2) The non-metal-doped titanium-based metal single-atom electrode material of the present invention has excellent decomposition activity for various complexed heavy metals and good stability. Therefore, the electrode material shows great application prospects in the deep treatment of complex industrial complexed wastewater.

[0039] 3) Non-metal-doped titanium-based metal single-atom electrodes are composed of cheap elements, are cheap, and have low production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1The phosphorus-doped titanium-based cobalt single-atom electrode (P-Co 1 -Ti) and the XRD patterns of Control Example 1, Control Example 2 and Control Example 3.

[0041] Figure 2 The P-Co prepared in Example 1 of the present invention 1 - X-ray energy spectrum (EDS mapping) of Ti electrode.

[0042] Figure 3 P-Co in Test Example 1 of the present invention 1 (a) Total nickel removal curve of electrochemical decomposition of Ni(II)-EDTA on Ti electrode, and (b) comparison of decomposition rate and total nickel removal performance among different electrodes.

[0043] Figure 4 P-Co in Test Example 1 of the present invention 1 - Cyclic stability test of electrochemical decomposition of Ni(II)-EDTA on Ti electrode.

[0044] Figure 5 P-Co in Test Example 1 of the present invention 1 -XRD spectra of the carbon felt cathode used for reduction and recovery of Ni in the Ni(II)-EDTA system with Ti electrode electrochemical decomposition before and after the reaction.

[0045] Figure 6 P-Co in Test Example 2 of the present invention 1 -Activity curves of electrochemical decomposition of Cu(II)-EDTA and Cr(III)-EDTA on Ti electrode.

[0046] Figure 7 (a) B-Co in Example 2 and Example 3 of the present invention 1 -Ti, and (b) S-Co 1 -Total nickel removal curve of electrochemical decomposition of Ni(II)-EDTA on Ti electrode.

[0047] Figure 8 The boron-doped titanium-based cobalt single-atom electrode (P-Fe 1 -Ti) and the XRD patterns of Control Example 4, Control Example 5 and Control Example 6.

[0048] Fig. 9 The P-Fe prepared in Example 4 of the method of the present invention 1 - X-ray energy spectrum (EDS mapping) of Ti electrode.

[0049] Fig.10The P-Fe in Test Example 3 of the present invention 1 (a) Total nickel removal curve of electrochemical decomposition of Ni(II)-EDTA on Ti electrode, and (b) comparison of decomposition rate and total nickel removal performance among different electrodes.

[0050] Fig.11 The P-Fe in Test Example 3 of the present invention 1 - Cyclic stability test of electrochemical decomposition of Ni(II)-EDTA on Ti electrode.

[0051] Fig.12 The P-Fe in Test Example 4 of the present invention 1 -Activity curves of electrochemical decomposition of Cu(II)-EDTA and Cr(III)-EDTA on Ti electrode.

[0052] Fig.13 (a) B-Fe in Example 5 and Example 6 of the present invention 1 -Ti, and (b) S-Fe 1 -Total nickel removal curve of electrochemical decomposition of Ni(II)-EDTA on Ti electrode. DETAILED DESCRIPTION

[0053] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0054] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are well known in the art.

[0055] Example 1

[0056] A method for preparing a phosphorus-doped titanium-based cobalt single-atom electrode comprises the following steps:

[0057] First, cut the titanium mesh into 2*2cm 2 Size, first pickled in 0.1 mol / L oxalic acid solution at 80°C for 30 minutes, then washed three times with ethanol and water respectively, and dried in an oven at 60°C. Prepare 3 mg / mL cobalt nitrate ethanol solution and 3 mg / mL sodium hypophosphite aqueous solution. Evenly drop 100 μL of cobalt nitrate solution on the titanium mesh and bake it under an infrared lamp. Drop 200 μL of sodium hypophosphite solution on a corundum magnetic boat and place it near the air inlet of the tubular furnace. Place the titanium mesh with cobalt nitrate dropwise on a magnetic boat near the air outlet. In an atmosphere of argon and / or nitrogen, treat at 300°C for 3 hours to prepare a phosphorus-doped titanium-based cobalt single atom electrode (P-Co 1 -Ti).

[0058] Characterization of physical properties of phosphorus-doped titanium-based cobalt single-atom electrode:

[0059] The phosphorus-doped titanium-based cobalt single-atom electrode synthesized in Example 1 was characterized by X-ray diffraction and X-ray electron spectroscopy mapping imaging technology. Figure 1 The XRD in the sample shows only the diffraction peak of the titanium substrate, indicating that there may be no cobalt or phosphorus nanoparticles on the electrode surface, which is consistent with Figure 2 Mapping showed that P and Co were evenly distributed on the surface of the material, proving that phosphorus-doped cobalt single-atom electrodes were successfully prepared.

[0060] Comparative Example 1

[0061] On the basis of Example 1, sodium hypophosphite was omitted to obtain a titanium-based cobalt single-atom electrode (Co 1 -Ti).

[0062] Comparative Example 2

[0063] On the basis of Example 1, the cobalt nitrate ethanol solution was omitted to obtain a phosphorus-doped titanium-based electrode (P-Ti).

[0064] Comparative Example 3

[0065] On the basis of Example 1, sodium hypophosphite and cobalt nitrate ethanol solution were omitted to obtain a titanium-based electrode (Ti).

[0066] Test Example 1

[0067] Test of the electrochemical decomposition performance of complexed heavy metals by phosphorus-doped titanium-based cobalt single-atom electrode in a single cell (single-chamber electrolytic cell):

[0068] Phosphorus-doped titanium-based cobalt single-atom electrode (P-Co 1 -Ti) as anode, carbon felt as cathode, mercury-mercurous sulfate electrode as reference electrode, reaction electrolyte is 0.05mol / L sodium sulfate solution; reaction potential is 1.1V, reaction time is 3h. In the wastewater, the heavy metal complex is nickel ethylenediaminetetraacetate (Ni(II)-EDTA), with a concentration of 10mg / L.

[0069] pass Figure 3 Discovery, P-Co 1 -Ti showed the best Ni(II)-EDTA decomposition and total Ni removal performance. Within 3 hours, the decomposition rate was close to 100%, and the total Ni removal rate was as high as 95.4%.

[0070] Figure 4 The cyclic stability test data show that P-Co 1 -Ti has a total nickel removal performance of more than 90% in 5 cycle tests, with good stability.

[0071] Figure 5Figure 2 shows the XRD spectra of the carbon felt cathode before and after the reaction, indicating that the Ni removed by electrochemical decomposition was reduced and fixed on the cathode carbon felt, realizing the deep treatment and resource recovery of the complexed heavy metal Ni(II)-EDTA.

[0072] Test Example 2

[0073] This embodiment provides a phosphorus-doped titanium-based cobalt single-atom electrode (P-Co 1 -Ti electrode) electrochemical decomposition method and application of other complexed heavy metals:

[0074] P-Co 1 -Ti as anode, carbon felt as cathode, mercury-mercurous sulfate electrode as reference electrode, reaction electrolyte is 0.05mol / L sodium sulfate solution; reaction potential is 1.05V, reaction time is 3h. In the wastewater, the heavy metal complexes are copper ethylenediaminetetraacetate (Cu(II)-EDTA) and chromium ethylenediaminetetraacetate (Cr(III)-EDTA), and the concentrations are 10mg / L respectively.

[0075] pass Figure 6 Discovery, P-Co 1 -Ti exhibited excellent Cu(II)-EDTA decomposition and total Cu removal performance; within 3 h, the decomposition rates of Cu(II)-EDTA and Cr(II)-EDTA were close to 100%.

[0076] Example 2

[0077] The preparation method of boron-doped titanium-based cobalt single-atom electrode comprises the following specific steps:

[0078] On the basis of Example 1, sodium hypophosphite was omitted, and 3 mg / mL boric acid aqueous solution was used as a boron source to replace the phosphorus source.

[0079] The specific preparation steps are as follows: 100 μL of cobalt nitrate solution is evenly applied to the titanium mesh, and then 100 μL of boric acid solution is applied to the titanium mesh, and then it is placed under an infrared lamp to dry until there is no obvious liquid. Then it is placed in a porcelain boat and placed in a tube furnace, and treated at 300°C for 3 hours in an argon and / or nitrogen atmosphere to prepare a boron-doped titanium-based cobalt single atom electrode (B-Co 1 -Ti).

[0080] The B-Co prepared in this example 1 -Ti electrode can also be used for electrochemical decomposition of complexed heavy metals (Ni(II)-EDTA, the test steps are the same as those in Test Example 1) ( Figure 7 a).

[0081] Example 3

[0082] The preparation method of sulfur-doped titanium-based cobalt single-atom electrode comprises the following specific steps:

[0083] On the basis of Example 1, sodium hypophosphite was omitted, and 3 mg / mL thiourea ethanol solution was used as the sulfur source to replace the phosphorus source.

[0084] The specific preparation steps are as follows: 100 μL of cobalt nitrate solution is evenly dropped onto the titanium mesh and dried under an infrared lamp until no obvious liquid is left. 200 μL of thiourea solution is dropped into a corundum magnetic boat and placed near the air inlet of the tube furnace. The titanium mesh with cobalt nitrate is placed in a magnetic boat near the air outlet. In an argon and / or nitrogen atmosphere, the titanium mesh is treated at 300°C for 3h to prepare a sulfur-doped titanium-based cobalt single atom electrode (S-Co 1 -Ti).

[0085] The S-Co prepared in this example 1 -Ti electrode can also be used for electrochemical decomposition of complexed heavy metals (Ni(II)-EDTA, the test steps are the same as those in Test Example 1) ( Figure 7 b).

[0086] Example 4

[0087] The preparation method of phosphorus-doped titanium-based iron single-atom electrode comprises the following specific steps:

[0088] On the basis of Example 1, 3 mg / mL ferric chloride hexahydrate ethanol solution was used as the iron source to replace the cobalt nitrate ethanol solution as the cobalt source.

[0089] The specific preparation steps are as follows: 100 μL of ferric chloride hexahydrate ethanol solution is evenly dripped onto the titanium mesh and dried under an infrared lamp until no obvious liquid is left. 200 μL of sodium hypophosphite is dripped into a corundum magnetic boat and placed near the air inlet of the tube furnace. The titanium mesh dripped with ferric chloride is placed in a magnetic boat near the air outlet. In an argon and / or nitrogen atmosphere, the titanium mesh is treated at 300°C for 3h to prepare a phosphorus-doped titanium-based single-atom iron electrode (P-Fe 1 -Ti).

[0090] The phosphorus-doped titanium-based single-atom iron electrode synthesized in Example 4 was characterized by X-ray diffraction and X-ray electron spectroscopy mapping imaging technology. Figure 8 The XRD in the sample shows only the diffraction peak of the titanium substrate, indicating that there may be no iron or phosphorus nanoparticles on the electrode surface, which is consistent with Fig. 9 Mapping showed that P and Fe were evenly distributed on the surface of the material, proving that phosphorus-doped iron single-atom electrode was successfully prepared.

[0091] Comparative Example 4

[0092] On the basis of Example 4, the sodium hypophosphite solution was omitted to obtain a titanium-based iron single-atom electrode (Fe1 -Ti)

[0093] Comparative Example 5

[0094] Based on Example 4, the ferric chloride solution was omitted to obtain a phosphorus-doped titanium-based electrode (P-Ti)

[0095] Comparative Example 6

[0096] On the basis of Example 4, ferric chloride and sodium hypophosphite solution were omitted to obtain a titanium-based electrode (Ti)

[0097] Test Example 3

[0098] Application of phosphorus-doped titanium-based iron single-atom electrode in single cell electrochemical decomposition of complexed heavy metals:

[0099] Phosphorus-doped titanium-based iron single-atom electrode (P-Fe 1 -Ti) as anode, carbon felt as cathode, silver-silver chloride electrode as reference electrode, reaction electrolyte is 0.05mol / L sodium sulfate solution; reaction potential is 1.8V, reaction time is 3h. In the wastewater, the concentration of nickel ethylenediaminetetraacetate (Ni(II)-EDTA) is 10mg / L.

[0100] pass Fig.10 It was found that P-Fe 1 -Ti showed the best Ni(II)-EDTA decomposition and total Ni removal performance. Within 3 hours, the decomposition rate was close to 100%, and the total Ni removal rate was as high as 95.7%.

[0101] Fig.11 The cyclic stability test data show that P-Fe 1 -Ti has a total nickel removal performance of more than 93% in 5 cycle tests, with good stability.

[0102] Test Example 4

[0103] This embodiment provides a phosphorus-doped titanium-based iron single-atom electrode (P-Fe 1 -Ti electrode) electrochemical decomposition method of other complexed heavy metals and its application

[0104] P-Fe 1 -Ti was used as the anode, carbon felt as the cathode, silver-silver chloride electrode as the reference electrode, the reaction electrolyte was 0.05 mol / L sodium sulfate solution; the reaction potential was 1.8 V, and the reaction time was 3 h. The heavy metal complexes were copper ethylenediaminetetraacetate (Cu(II)-EDTA) and chromium ethylenediaminetetraacetate (Cr(III)-EDTA), and the concentrations were 10 mg / L respectively.

[0105] pass Fig.12 It was found that P-Fe 1 -Ti showed the best performance in Cu(II)-EDTA decomposition and total Cu removal. Within 3 h, the decomposition rates of Cu(II)-EDTA and Cr(II)-EDTA were close to 100%.

[0106] Example 5

[0107] The preparation method of boron-doped titanium-based iron single-atom electrode comprises the following specific steps:

[0108] On the basis of Example 4, sodium hypophosphite was omitted, and 3 mg / mL boric acid aqueous solution was used as the boron source to replace the phosphorus source.

[0109] The specific preparation steps are as follows: 100 μL of ferric chloride hexahydrate solution is evenly dripped onto the titanium mesh, and after drying, 200 μL of boric acid solution is dripped, and the mesh is placed under an infrared lamp to dry until there is no obvious liquid. Then, it is placed in a porcelain boat and placed in a tube furnace, and treated at 300°C for 3 hours in an argon and / or nitrogen atmosphere to prepare a boron-doped titanium-based single-atom iron electrode (B-Fe 1 -Ti).

[0110] The B-Fe prepared in this example 1 -Ti electrode can also be used for electrochemical decomposition of complexed heavy metals (Ni(II)-EDTA, the test steps are the same as those in Test Example 3) ( Fig.13 a).

[0111] Example 6

[0112] The preparation method of sulfur-doped titanium-based iron single-atom electrode comprises the following specific steps:

[0113] On the basis of Example 4, sodium hypophosphite was omitted, and 3 mg / mL thiourea ethanol solution was used as the sulfur source to replace the phosphorus source.

[0114] The specific preparation steps are as follows: 100 μL of ferric chloride hexahydrate solution is evenly dropped onto the titanium mesh and placed under an infrared lamp to dry until no obvious liquid is present. 200 μL of thiourea is dropped into a corundum magnetic boat and placed near the air inlet of the tube furnace. The titanium mesh with ferric nitrate is dropped into a magnetic boat near the air outlet. In an argon and / or nitrogen atmosphere, the titanium mesh is treated at 300°C for 3h to prepare a sulfur-doped titanium-based iron single atom electrode (S-Fe 1 -Ti).

[0115] The S-Fe prepared in this example 1 -Ti electrode can also be used for electrochemical decomposition of complexed heavy metals (Ni(II)-EDTA, the test steps are the same as those in Test Example 3) ( Fig.13 b).

[0116] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals, characterized in that: It includes a titanium substrate, and non-metal atoms and metal single atoms respectively loaded on the surface of the titanium substrate; The non-metal atom is selected from one or more of phosphorus, boron and sulfur; The metal single atom is selected from one or both of iron and cobalt.

2. The non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 1, characterized in that: The titanium substrate includes titanium mesh, titanium felt and titanium foam; the doping amount of the non-metallic atoms is 0.02-0.5wt% of the total mass of the electrode; and the doping amount of the metal single atom is 0.02-0.5wt% of the total mass of the electrode.

3. A method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals as claimed in claim 1 or 2, characterized in that: If the non-metal atom is phosphorus and / or sulfur, the preparation method comprises the following steps: Placing a non-metallic precursor solution at the air inlet of a tube furnace; uniformly dripping a metal precursor solution on the surface of a titanium substrate, and placing it at the air outlet of a tube furnace after drying; performing pyrolysis under a protective atmosphere to obtain the electrode; If the non-metal atom is boron, the preparation method comprises the following steps: The metal precursor solution is evenly dripped onto the surface of the titanium substrate, and then the non-metal precursor solution is dripped onto the surface of the titanium substrate, and infrared heating and pyrolysis are performed under a protective atmosphere to obtain the electrode.

4. The method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 3, characterized in that: The metal precursor solution is a chloride, a nitrate or an acetate of a metal, and the concentration of the metal precursor solution is 0.5-10 mg / mL.

5. The method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 3, characterized in that: The non-metal precursor solution: if the non-metal atom is phosphorus, the non-metal precursor is phosphite; if the non-metal atom is sulfur, the non-metal precursor is at least one of thiourea, sodium sulfide and sulfur powder; if the non-metal atom is boron, the non-metal precursor is boric acid or boron oxide; the concentration of the non-metal precursor solution is 3 to 30 mg / mL.

6. The method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 3, characterized in that: If the non-metal atom is phosphorus and / or sulfur, the mass ratio of the non-metal precursor to the metal precursor is 2 to 12:1; if the non-metal atom is boron, the mass ratio of the non-metal precursor to the metal precursor is 1 to 6:

1.

7. The method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 3, characterized in that: The protective atmosphere is an argon atmosphere and / or a nitrogen atmosphere.

8. The method for preparing a non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals according to claim 3, characterized in that: The pyrolysis temperature is 200-500° C. and the time is 2-5 hours.

9. Use of the non-metal-doped titanium-based metal single-atom electrode for decomplexing heavy metals as claimed in claim 1 or 2 in the treatment of heavy metal complex wastewater.

10. The use according to claim 9, characterized in that: A three-electrode system was used for electrochemical complex breaking; In the three-electrode system: The working electrode is the electrode as claimed in claim 1 or 2; the reference electrode is selected from a silver-silver chloride electrode; the counter electrode is selected from one of carbon felt, carbon cloth, graphite sheet and titanium mesh; the electrolyte is a sodium sulfate solution; In the electrochemical network breaking: The applied voltage is 0.8 to 3.0 V, and the reaction time is 1 to 3 hours.

Citation Information

Patent Citations

  • Preparation of phosphorus-doped titanium black / foam titanium electrode and method for treating heavy metal wastewater by using phosphorus-doped titanium black / foam titanium electrode

    CN115925056A

  • Cathode electric field enhanced ozone oxidation complex breaking and metal synchronous recovery device and method

    CN111977751A

  • Phosphorus and nitrogen co-doped iron monatomic carbon material as well as preparation method and application thereof

    CN112938966A

  • Monatomic electrode and preparation method and application thereof

    CN114162907A

  • Electrochemical efficient dehalogenation electrode for organic halogenated pollutants as well as preparation method and application of electrochemical efficient dehalogenation electrode

    CN115448428A

Cited By

  • Foamed titanium-based iodine iron double-monatomic electrode, preparation thereof and application of foamed titanium-based iodine iron double-monatomic electrode in preparation of singlet oxygen

    CN120006326A